ANALISIS DAMPAK PENGIRIMAN TERNAK TERHADAP KESEJAHTERAAN PENGUSAHA LOKAL : STUDI KUALITATIF DI KABUPATEN SUMBAWA BARAT - Cahaya Haerani; Sri Rahayu (Pusat Riset dan Publikasi, 2025)
This study aims to examine the socio-economic dynamics and changing well-being of livestock entrepreneurs in West Sumbawa Regency within the context of inter-island livestock shipment, a strategic sector that serves as a key driver of the regional economy. Using a qualitative approach involving in-depth interviews and participatory observations with livestock entrepreneurs, small-scale farmers, and other relevant stakeholders, the research explores how actors navigate challenges such as price fluctuations, limited infrastructure, unequal market access, and the complexity of local regulatory frameworks. The study employs a qualitative research design, with data analysis encompassing iterative processes of data reduction, data display, and conclusion drawing until saturation is achieved, while validity is strengthened through triangulation and repeated verification with informants. The findings indicate that livestock shipment activities produce dual effects: they expand income opportunities through broader market access, yet simultaneously generate vulnerabilities for small-scale entrepreneurs due to the absence of standardized livestock quality, price uncertainties, and the dominance of larger capital holders. Government roles in issuing shipment recommendations, conducting animal health inspections, and regulating quotas are shown to be crucial in ensuring legal compliance, population stability, and smooth distribution flows, although administrative constraints and uneven service quality continue to pose challenges. Overall, the study highlights that the sustainability of the livestock shipment sector is significantly shaped by the interaction between social capital, entrepreneurs’ adaptive capacities, and the effectiveness of public policies capable of protecting all actors within the livestock value chain, thereby enhancing the well-being of livestock-dependent communities in an inclusive and sustainable manner.